Penerapan Teknologi Tepat Guna untuk Mendukung Ketahanan Air Bersih di Ngoresan, Surakarta - Jarwanto, Jarwanto; Rakhman, Arie Noor; Maulana, Fivry Wellda (-, 2025)
Meeting clean water needs in densely populated areas such as Ngoresan, Surakarta City, is a major challenge, especially during the dry season when well discharge declines. This community service initiative aims to enhance clean water resilience in Ngoresan through the application of groundwater drilling technology informed by geological studies. The activities include site survey, equipment installation, drilling, aquifer identification, water quality analysis, community education, and joint evaluation. Drilling identified a productive aquifer at a depth of 25.7 meters within Merapi volcanic rock, with the final well reaching 62.5 meters. Water quality analysis confirmed it is safe for consumption. Community participation in education and facility maintenance strengthens the sustainability of the program. This initiative not only provides a reliable water source but also fosters awareness of groundwater conservation and the risks of over-extraction, thereby enhancing local resilience in water availability.